Agrarian Justice and Contextuality in Maxim Fiat Justitia Ruat Caelum and Fiat Justitia Ne Pereat Mundus - Muh. Afif Mahfud; Erlyn Indarti; Sukirno Sukirno (Universitas Syiah Kuala, 2021)
Maxim is a short sentence with deep meaning related to value and purpose of law include agrarian law. This article analyse the meaning of fiat justitia ruat caelum and fiat justitia ne pereat mundus as well as its relation to agrarian justice and its contextuality. Both of those maxim are paradigmatically analysed. This is a normative juridical research, use conceptual and historical approach with secondary data then qualitatively analysed. Concluded that fiat justitia ruat caelum and fiat justitia pereat mundus is part of legal formalism. The agrarian justice is achieved when the law is enforced as the text and its acontextual. In contrast, fiat justitia ne pereat mundus consider law is valid when it is according to the purpose and agrarian justice exist when it bring out prosperity for all people. Paradigmatically, fiat justicia ruat caelum and fiat justitia pereat mundus fall in positivism paradigm, consider rule is perfect, no interpretation, separation of law and morality, impossibility of interdisciplinary approach. In another hand, fiat justitia ne pereat mundus falls in post positivism paradigm which consider law is imperfect, interpretation is possible, no separation of law and morality and interdisciplinary approch is opened. The law is acontextual.